"All emigrants are up to the physical, mental, and moral standards required": A tale of two child rescue schemes. Issue 3 (8th February 2022) - Sims‐Schouten, Wendy; Weindling, Paul
Abstract: The current paper critically assesses and reflects on the ideals and realities of two major (British) child migration schemes, namely the British Home Child scheme (1869–1930) and the Kindertransport scheme (1938–1940), to add to current understandings of their place within wider international histories of child migration, moral reforms, eugenics, settlement, and identity. Specifically, we focus on constructions of "mentally and physically deficient" children/young people, informed by eugenic viewpoints and biological determinism, and how this guided inclusion and exclusion decisions in both schemes. Both schemes made judgements regarding which children should be included/excluded in the schemes or returned to their country of origin (as was the case with children in the Canadian child migration scheme) fueled by a type of eugenics oriented to transplanting strong physical and psychologically resilient specimens. By viewing the realities of the child migration schemes, including the varied experiences and narratives in relation to child migrants, in light of eugenicist narratives of difference, pathology, victimhood, and contamination, we shed a light on uneven practices, formations of power, and expectations of the times.